Roles of the wound hormone jasmonate in plant regeneration. (20th November 2021) - Zhang, Guifang; Liu, Wu; Gu, Zewei; Wu, Shasha; E, Yilan; Zhou, Wenkun; Lin, Jinxing; Xu, Lin
Abstract: Plants have remarkable abilities to regenerate in response to wounding. How wounding triggers rapid signal transduction to induce a cellular response is a key topic for understanding the molecular mechanism of plant regeneration. An increasing body of evidence indicates that jasmonate, a hormone that is produced rapidly in response to wounding, plays multiple roles in different plant regeneration processes. In this review, we summarize recent advances on the roles of jasmonate in tissue repair, the formation of wound-induced callus, de novo organ regeneration, and somatic embryogenesis. Physiological and molecular analyses indicate that jasmonate can regulate stem cell activities, cell proliferation, cell fate transition, and auxin production, thereby contributing to plant regeneration. In addition, jasmonate is strictly controlled in plant cells via restriction of the jasmonate concentration and its signalling pathway in a spatial and temporal manner during regeneration. Overall, jasmonate acts as the hormone linking wounding to distinct types of regeneration in plants. Abstract : Wounding triggers plant regeneration. Here, we review how jasmonate links wounding to cell fate transition during plant regeneration, and how it is strictly controlled to avoid hypersensitivity to wounding.